2010
DOI: 10.1002/cphc.201000174
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surface Composition of Nanoparticles on their Interactions with Serum Albumin

Abstract: Interactions between differently functionalised silver and gold nanoparticles (NPs) as well as polystyrene nanoparticles with bovine serum albumin (BSA) are studied using circular dichroism (CD) spectroscopy. It is found that the addition of NPs to the protein solution destroys part of the helical secondary structure of the protein as a result of surface adsorption. From the loss of free protein and hence the extent of their structural change adsorption equilibrium constants are derived. The results reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
112
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 73 publications
8
112
1
2
Order By: Relevance
“…A layer of proteins forms on the NP surfaces, the so-called protein corona [10,[31][32][33][34][35][36][37][38][39][40][41][42][43]. Consequently, cell surface receptors, which activate the endocytosis machinery, actually encounter NPs enshrouded in biomolecules rather than bare particles.…”
Section: Introductionmentioning
confidence: 99%
“…A layer of proteins forms on the NP surfaces, the so-called protein corona [10,[31][32][33][34][35][36][37][38][39][40][41][42][43]. Consequently, cell surface receptors, which activate the endocytosis machinery, actually encounter NPs enshrouded in biomolecules rather than bare particles.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous toxicological studies have revealed that nanoparticles are much more reactive and toxic than larger particles made from the same material [6][7][8][9][10]. It is therefore of paramount interest to characterize NP suspensions in salt-containing environments and to ultimately also assess the influence of biomolecules on their behavior [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, it is possible that proteins do denature or unfold upon binding or adsorbing to NPs [24,25]. For instance, using albumin alone Treuell et al found that the α -helical structures of albumin are destroyed in the presence of 20 nm citrated gold and silver NPs while it does not with polymeric NPs [24].…”
Section: Blood Protein-np Interactionsmentioning
confidence: 99%
“…For instance, using albumin alone Treuell et al found that the α -helical structures of albumin are destroyed in the presence of 20 nm citrated gold and silver NPs while it does not with polymeric NPs [24]. Zhang and colleagues also demonstrated aggregate formation with DLS, TEM and fluorescence microscopy in the lysozyme solution when incubated with GNPs (90 nm citrate stabilized) [25].…”
Section: Blood Protein-np Interactionsmentioning
confidence: 99%